Wizerunek Seneki w tragedii Oktawia i w Rocznikach Tacyta - Pigoń, Jakub (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The paper examines the representation of Seneca in two literary works of the late 1st and early 2nd cent. AD, the anonymous tragedy Octavia and the Annals by Tacitus. In the Octavia Seneca appears as the emperor Nero’s upright but unhappy teacher trying in vain to inculcate salutary advice to his master. There is no question of his being responsible for the crimes of Nero; the picture of him drawn in the play is wholly favourable. The portrayal of Seneca in Tacitus’ Annals is more complex and nuanced, and only seldom the historian gives his own views about Nero’s advisor. However, it would be wrong to suppose that Seneca is harshly criticised by Tacitus.
The Portrayal of Seneca in the Octavia and in Tacitus’ Annals
The paper examines the representation of Seneca the Younger in two literary texts written a few decades after his death, the anonymous tragedy Octavia (perhaps 68/69 AD, wrongly attributed to Seneca) and the historical work by Tacitus, the Annals (early 2nd cent. AD). These two texts give the most detailed picture of Seneca in Roman literature; although belonging to different literary genres, they show some interesting points of contact. In the Octavia Seneca is introduced as the emperor Nero’s upright but unhappy teacher trying in vain to persuade his master that the best method of government is mildness and kindness towards one’s subjects. (In particular, he seeks to discourage Nero from divorcing Octavia and marrying Poppaea Sabina.) There are some significant echoes of Seneca’s writings, especially De clementia, and, interestingly, it is the play’s Nero, not Seneca, who is closer to the philosopher’s argument in De clem. I 9–10 (cf. Oct. 472–529). The two key words of the Seneca–Nero exchange are licet and decet and the emperor manages to play Seneca’s notion that “id facere laus est quod decet, non quod licet” against his teacher (cf. Oct. 454 and 457). In spite of this, the playwright’s portrayal of Seneca is wholly favourable. The philosopher is unable to prevail upon the emperor, but this is by no means his fault; there is no question of his being responsible for Nero’s crimes. Seneca courageously speaks his mind (and the Seneca–Nero scene ends with a foreshadowing of his being killed by the emperor); there is not even a hint of his hypocrisy and double standards, a reproach quite often levelled at him both in antiquity and in modern times. The portrayal of Seneca in Tacitus’ Annals is more complex and nuanced, but it should not be regarded as internally incoherent (due to the historian’s shift from one source to another or to the lack of revision of the Annals). The complexity of Tacitus’ picture of Seneca is, above all, the consequence of the fact that the teacher of Nero was, in the historian’s eyes, a complex character. Interestingly, Tacitus presents him mainly through the eyes of others (Agrippina the Younger, Suillius Rufus, Nero’s malicious associates, anonymous Romans, etc.) and only seldom reveals his own views about Seneca’s actions and character. However, from a few passages where Seneca is introduced by Tacitus himself, without the mediation of other historical figures, it is possible to come to some important conclusions about the historian’s attitude. In the paper, three such passages are analyzed: Ann. XIII 2, 1–2; XIV 52, 1; and XV 23, 4. Especially significant is the last one, recounting an episode in which Seneca is linked to Thrasea Paetus. The phrase egregii viri, used here in reference to the both politicians, is, by Tacitus’ standards, a lavish praise – and deserves not to be overlooked by those who think that the historian is highly critical of Seneca.
Keywords: Seneca the Younger; Roman literature (1st and 2nd cent. AD) Roman Empire; Tacitus; Octavia Praetexta; Nero; characterization in literature